On the identity of Microananteris, with a discussion on pectinal morphology, and description of a new Ananteris from Brazil (Scorpiones, Buthidae) (2011)
The characters originally used to define the monotypic genus Microananteris Lourenço, 2003 are reanalyzed from the point of view of their usefulness to justify its recognition as a genus apart from Ananteris Thorell, 1891. A study of pectinal morphology conducted with Scanning Electron Microscopy (SEM) in six species of Ananteris, along with the results presented by Lourenço (2003) and other authors, demonstrate that both genera cannot be separated based on the shape of the peg sensillae but demonstrate this character’s (and the presence of seta-like structures) immediate usefulness at the species level instead. Such analysis of the morphological attributes of Microananteris as defined by Lourenço (2003) reveals there is no evidence in support of its validity. Therefore, Microananteris is synonymized with Ananteris and Microananteris minor Lourenço, 2003 transferred to this genus. A new species of Ananteris is also described from the Natural Reserve Palmari in the Brazilian Amazon.